Familial occurrence of complement dysfunction in Crohn's disease: correlation with intestinal symptoms and hypercatabolism of complement. Issue 2 (February 1985) - Elmgreen, J; Both, H; Binder, V
Abstract : Complement was studied in Crohn's disease probands with early onset and in their first degree relatives. Controls included 24 healthy volunteers and 24 patients with ulcerative colitis or peptic ulcers. Subnormal generation of chemotactic activity by the alternative pathway was shown in eight of 21 probands and in six of 33 relatives, a frequency in both groups significantly different from controls (p less than 0.005), with a strong connection between findings in patients and relatives. As previously shown in patients with Crohn's disease, the subnormal generation was related to decreased utilisation of complement C3 in relatives. Raised levels of circulating complement C3c split products suggested complement involvement in Crohn's disease probands. In contrast, plasma C3c was normal in all relatives, and none of the six cases with complement dysfunction had gastrointestinal symptoms or a history of inflammatory bowel disease. Our data suggest, that complement abnormality seen in Crohn's disease patients does not simply reflect mucosal inflammation or hypercatabolism of complement.